Serological survey of Neospora caninum infection in dairy cattle - Aktas, F.; Vural, G.; Sezen, I. Y. (Indian Veterinary Journal, 2007)
Neospora caninum is a coccidian parasite of cattle, sheep, goats, horses and dogs. Infection is associated with bovine abortion and neonatal mortality (Dubey, 2003) In Turkey, prevalence of Neosporosis in cows was determined as 5.46 - 32.82% in different provinces in central Anatolia (Biyikoglu et al. 2001); 7.5 % in Sanliurfa (Sevgili et al., 2005); 9.2% in Sakarya (Oncel and Biyikoglu, 2003) and 5.6 - 10% in some provinces of Thrace (Biyikoglu et al., 2005). Neosporosis was also reported in dogs in Turkey (Coskun et al., 2000). The objective of this study was to evaluate the significance of neosporosis in cows in Gebze.
Keywords: Seroprevalence